Analysis of the Relationship between Environmental Conditions and CO2 Concentration in the Teaching Classrooms of a Secondary Educational Institution - Gonzales Medina, Luz Eleana; Paz Corrales, Olivia Anyelina; Gamarra Andía, Dana Sofia; Apaza Calla, Fernando Socarraz (LACCEI, 2025)
The arrival of COVID-19 posed a very important challenge for educational institutions, causing them to adopt different measures to guarantee healthy environments for a safe return to classes. However, knowledge about CO2 as an indicator to know the conditions of air quality and the conditions it modifies with its presence was a mystery until the arrival of the pandemic. That is why, the objective of the present study seeks to analyze the relationship between environmental conditions and the concentration of this gas within the classrooms of a secondary educational institution, located in the city of Arequipa. The methodology used consisted of a non-experimental analysis, of correlational scope, obtaining the data through documentation, monitoring and observation of the 5 classrooms of the institution, finalizing its determination through the calculation of Pearson correlation coefficients. The results showed that there is a correlation between the variables, with temperature and CO2 maintaining a strong positive relationship; unlike humidity, which demonstrates a strong negative relationship. Furthermore, about the percentage of occupancy and the opening of ventilation, the concentration of CO2 varies in a direct and inverse proportion respectively. Finally, it is concluded that there is a relationship between the variables, where the measurement of the concentration of carbon dioxide turns out to be an adequate indicator to determine the quality of indoor air in classrooms by not exceeding the permitted threshold of 400 ppm, therefore special emphasis must be placed on the management of environmental conditions to avoid its variation.